2017
DOI: 10.1002/cbdv.201700006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antibacterial, Antibiofilm and Synergistic Properties of Essential Oils from Eucalyptus globulus Labill. and Seven Mediterranean Aromatic Plants

Abstract: Essential oils (EOs) from Eucalyptus globulus Labill. ssp. globulus and from Mediterranean autochthonous aromatic plants - Thymus mastichina L., Mentha pulegium L., Rosmarinus officinalis L., Calamintha nepeta (L.) Savi ssp. nepeta, Cistus ladanifer L., Foeniculum vulgare L., Dittrichia viscosa (L.) Greuter ssp. viscosa - were extracted by hydrodistillation and characterized by GC-FID and NMR spectroscopy. EOs were evaluated for antimicrobial properties against several bacterial strains, using diverse methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 40 publications
5
23
1
5
Order By: Relevance
“…Zidane et al . and Vieira et al . found that Cis.la‐EO was rich in α ‐pinene and camphene while Gomes, Mata, and Rodrigues reported viridifloral and globulol as the major components.…”
Section: Resultsmentioning
confidence: 97%
“…Zidane et al . and Vieira et al . found that Cis.la‐EO was rich in α ‐pinene and camphene while Gomes, Mata, and Rodrigues reported viridifloral and globulol as the major components.…”
Section: Resultsmentioning
confidence: 97%
“…Essential oils are complex mixtures of volatile organic substances, consisting of oxygenated compounds and hydrocarbons, such as sesquiterpenes and monoterpenes, were widely applied in food, perfumes, toiletries, chemical additives, medicine and pharmaceutical science . Many plant essential oils and their major constituents exhibit a wide range of biological properties, such as insecticidal, antibacterial, antifungal, spasmolytic, and so on . Due to the great value, the development of essential oils from plants and evaluation on their activities is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…C. ladanifer shows a different terpene profile from other Cistus species, with a close taxonomic relationship (Gulz 1984;Oller-López et al 2005). Regarding mono-and sesquiterpenes, the most common reported major compounds are the monoterpenes α-pinene (Gomes et al 2005;Gulz 1984;Mariotti et al 1997;Rincón et al 2000;Robles et al 2003;Teixeira et al 2007;Vieira et al 2017), camphene (Zidane et al 2013) and pinocarveol (Oller-López et al 2005;Verdeguer et al 2012) and the sesquiterpene viridiflorol (Gomes et al 2005;Greche et al 2009;Weyerstahl et al 1998). In their literature review, Gomes et al (2005) also observed that α-pinene was the most commonly reported major compound.…”
Section: Odoriferous Compoundsmentioning
confidence: 98%
“…Another important compound found in high proportions in C. ladanifer extracts is the carotenoid derivative norisoprene called 2,2,6-trimethylcyclohexanone (Gomes et al 2005;Greche et al 2009;Mariotti et al 1997;Oller-López et al 2005;Ramalho et al 1999;Robles et al 2003;Santos et al 2017;Teixeira et al 2007;Verdeguer et al 2012;Weyerstahl et al 1998;Zidane et al 2013), which is one Barros et al (2013); Chaves et al (1997aChaves et al ( , b, 1998Chaves et al ( , 2001); Fernández-Arroyo et al 2010; Guimarães et al (2009); Gomes et al (2005); Greche et al (2009); Gulz (1984); Mariotti et al (1997);Oller-López et al (2005); Pascual et al (1982); Proksch and Gulz (1980a, b); Ramalho et al (1999); Rincón et al (2000); Robles et al (2003); Santos et al (2017); Sosa et al (2004); Teixeira et al (2007); Verdeguer et al (2012); Vieira et al (2017); Vogt et al (1987); Weyerstahl et al (1998); Wollenweber and Mann (1984) Extracts (Gomes et al 2005;Greche et al 2009;Gulz 1984;Mariotti et al 1997;…”
Section: Odoriferous Compoundsmentioning
confidence: 99%